Constitutional and legal regulation freedom of labor (Journal of actual problems of jurisprudence, 2019)
This article discusses the current issues of freedom of labor. The authors examine the problems encounteredin the implementation of the right to freedom of labor. The article also discusses the features of security andprotection of the right to freedom of labor. The authors provide recommendations to improve the legislationof Kazakhstan in the sphere of ensuring the right to freedom of labor.Keywords: freedom of labor, right to work, contract, law, trade unions.